ANALISIS WACANA KRITIS VAN DIJK PEMBERITAAN PERINGATAN DARURAT DAN KEKERASAN APARAT KOMPAS.COM - Haryadi, Mukti; Hamdani, Agus (Jurnal Membaca Bahasa dan Sastra Indonesia, 2024)
This study analyzes the discourse of news coverage on police violence during the “Peringatan Darurat” protests in various Indonesian cities on August 23, 2024, published by Kompas.com. Using Teun A. Van Dijk’s Critical Discourse Analysis (CDA) model, the research examines how the media represents police violence and public responses. This qualitative study employs a descriptive-analytical method, using the article titled “Aksi Peringatan Darurat” dan Kekerasan Aparat yang Berulang as its primary source. Data analysis focuses on the text’s macrostructure, superstructure, and microstructure. The findings reveal well-organized discourse structures: the macrostructure highlights police violence in response to protests against the DPR’s rejection of the Constitutional Court’s decision. The superstructure systematically presents event details, while the microstructure influences public opinion, supporting protests. Ideologically, the news reflects student resistance to the DPR’s stance. Through Van Dijk’s CDA, this study uncovers textual dimensions of the Kompas.com article.